A state of reversible compensated ventricular dysfunction precedes pathological remodelling in response to cardiomyocyte-specific activity of angiotensin II type-1 receptor in mice - Georgia A. Frentzou; Mark J. Drinkhill; Neil A. Turner; Stephen G. Ball; Justin F. X. Ainscough (The Company of Biologists, 2015)
Cardiac dysfunction is commonly associated with high-blood-pressure-induced cardiomyocyte hypertrophy, in response to aberrant renin-angiotensin system (RAS) activity. Ensuing pathological remodelling promotes cardiomyocyte death and cardiac fibroblast activation, leading to cardiac fibrosis. The initiating cellular mechanisms that underlie this progressive disease are poorly understood. We previously reported a conditional mouse model in which a human angiotensin II type-I receptor transgene (HART) was expressed in differentiated cardiomyocytes after they had fully matured, but not during development. Twelve-month-old HART mice exhibited ventricular dysfunction and cardiomyocyte hypertrophy with interstitial fibrosis following full receptor stimulation, without affecting blood pressure. Here, we show that chronic HART activity in young adult mice causes ventricular dysfunction without hypertrophy, fibrosis or cardiomyocyte death. Dysfunction correlated with reduced expression of pro-hypertrophy markers and increased expression of pro-angiogenic markers in the cardiomyocytes experiencing increased receptor load. This stimulates responsive changes in closely associated non-myocyte cells, including the downregulation of pro-angiogenic genes, a dampened inflammatory response and upregulation of Tgfβ. Importantly, this state of compensated dysfunction was reversible. Furthermore, increased stimulation of the receptors on the cardiomyocytes caused a switch in the secondary response from the non-myocyte cells. Progressive cardiac remodelling was stimulated through hypertrophy and death of individual cardiomyocytes, with infiltration, proliferation and activation of fibroblast and inflammatory cells, leading to increased angiogenic and inflammatory signalling. Together, these data demonstrate that a state of pre-hypertrophic compensated dysfunction can exist in affected individuals before common markers of heart disease are detectable. The data also suggest that there is an initial response from the housekeeping cells of the heart to signals emanating from distressed neighbouring cardiomyocytes to suppress those changes most commonly associated with progressive heart disease. We suggest that the reversible nature of this state of compensated dysfunction presents an ideal window of opportunity for personalised therapeutic intervention.